NLRP3 Activation Was Regulated by DNA Methylation Modification during Mycobacterium tuberculosis Infection. (6th June 2016) - Wei, Meili; Wang, Lu; Wu, Tao; Xi, Jun; Han, Yuze; Yang, Xingxiang; Zhang, Ding; Fang, Qiang; Tang, Bikui
Abstract : Mycobacterium tuberculosis (Mtb) infection activates the NLRP3 inflammasome in macrophages and dendritic cells. Much attention has been paid to the mechanisms for regulation of NLRP3 against Mtb. However, whether epigenetic mechanisms participated in NLRP3 activation is still little known. Here we showed that NLRP3 activation was regulated by DNA methylation modification. Mtb infection promoted NLRP3 activation and inflammatory cytokines expression. NLRP3 promoter was cloned and subsequently identified by Dual-Luciferase Reporter System. The results showed that NLRP3 promoter activity was decreased after methylation by DNA methylase Sss I in vitro . Meanwhile, DNA methyltransferases inhibitor DAC could upregulate the expression of NLRP3. Furthermore, promoter region of NLRP3 gene was demethylated after Mtb H37Rv strain infection. These data revealed that DNA methylation was involved in NLRP3 inflammasome activation during Mtb infection and provided a new insight into the relationship between host and pathogens.